STRATEGI KOMUNIKASI PEMASARAN ONLINE SHOP “QUEENBEA” TERHADAP KEPUTUSAN PEMBELIAN PRODUK AKSESORIS DI E-COMMERCE SHOPEE - Dela Rahmah Aminarti; Qoniah Nur Wijayani (JOURNAL SAINS STUDENT RESEARCH, 2024)
Research was conducted to determine marketing communication strategies regarding product purchasing decisions. The ease of marketing products today is due to the increasing development of technology, making online shopping increasingly popular with consumers. Due to its effectiveness in shopping without having to meet face to face, convenience in time, fast transactions, access to selecting the items you want and need are all easy. This also makes competition tougher in sales in online shops. This research examines the Marketing Communication Strategy of the Online Shop "Queenbea" in E-commerce Shopee. This research aims to explain the marketing communication strategies for the online shop "Queenbea" on Shopee.